2018
DOI: 10.1017/s0305000917000514
|View full text |Cite
|
Sign up to set email alerts
|

The role of sublexical variables in reading fluency development among Spanish children

Abstract: Several studies have found that, after repeated exposure to new words, children form orthographic representations that allow them to read those words faster and more fluently. However, these studies did not take into account variables related to the words. The aim of this study was to investigate the influence of sublexical variables on the formation of orthographic representations of words by Spanish children. The first experiment used pseudo-words of varying syllabic structure and syllabic frequency. The sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
3
17
0
1
Order By: Relevance
“…• Appropriate pauses (i.e., pauses made when a punctuation mark, such as a full stop, comma and colon is encountered). Experienced readers make shorter appropriate pauses while reading (Álvarez-Cañizo et al, 2015(Álvarez-Cañizo et al, , 2018Miller & Schwanenflugel, 2006, 2008Schwanenflugel et al, 2004). • Inappropriate pauses (i.e., pauses made in the absence of a punctuation mark indicating a break, whether between words, within words or at the end of a line in the printed text).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Appropriate pauses (i.e., pauses made when a punctuation mark, such as a full stop, comma and colon is encountered). Experienced readers make shorter appropriate pauses while reading (Álvarez-Cañizo et al, 2015(Álvarez-Cañizo et al, , 2018Miller & Schwanenflugel, 2006, 2008Schwanenflugel et al, 2004). • Inappropriate pauses (i.e., pauses made in the absence of a punctuation mark indicating a break, whether between words, within words or at the end of a line in the printed text).…”
Section: Methodsmentioning
confidence: 99%
“…With this in mind, a number of studies of reading prosody have been conducted with Spanish children. Álvarez-Cañizo, et al (2018) compared the reading aloud of third-grade and fifth-grade children with that of an adult sample, using a text that manipulated the type and length of the sentences but not other variables such as word type, word frequency or syntactic structure of sentences. The results showed that children from both grades made longer inappropriate pauses than did adults and that third graders also made more inappropriate pauses than fifth graders and adults.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, even in transparent orthographies, children also develop representations for intermediate units (Burani et al, 2002;Cuetos and Suárez-Coalla, 2009), and for whole words (Suárez-Coalla et al, 2016). It has been reported that several variables modulate orthographic storing, including, for example, syllable structure, context-dependent graphemes, and phonological or semantic knowledge of new words (Bowey, 1995;Walley et al, 2003;Ricketts et al, 2007;Wang et al, 2013;Álvarez-Cañizo et al, 2018). The development of reading fluency therefore depends on many variables.…”
Section: Reading Acquisitionmentioning
confidence: 99%
“…Given that orthographic learning seems to be reflected in the accuracy and speed of reading (Álvarez‐Cañizo, Suárez‐Coalla, & Cuetos, submitted), it seems plausible that the formation of orthographic representations is critically influenced by syllable characteristics. Our goal, therefore, was to assess whether syllabic frequency and complexity influence orthographic learning in children with dyslexia.…”
mentioning
confidence: 99%